The Implementation of Problem Based Learning and Window Shopping Model for Improving Students' Communication Skills - Ro'i Khatul Jannah; Helmi Auliya; Deni Setiawan; Edi Waluyo (International Journal of Active Learning, 2023)
This research aims to enhance the communication skills of students in Grade VII J during the second semester of the academic year 2022/2023 at SMPN 2 Tengaran. The study was conducted using the Problem Based Learning model and the Window shopping method. It employed a classroom action research design based on the Kemmis and Taggart model, which consisted of two cycles. Each cycle included observation, planning, implementation, evaluation, and reflection phases. The research data comprised observations of students' communication skills, which were collected during the learning process by two observers. Comparative descriptive analysis was employed to analyze the data between cycles. The results of the study revealed that the average communication skills of students were 42% in the pre-cycle, 60% in Cycle I, and 82.5% in Cycle II. Based on these findings, it can be concluded that the implementation of Problem Based Learning and the Window shopping method can improve the communication skills of Grade VII J students at SMPN 2 Tengaran.